Tailoring the chemical and structural properties of graphene oxide nanoplatelets synthesised at room temperature with different processing times - Toh, Guat Yee (Animo Repository, 2017)
© Penerbit Universiti Sains Malaysia, 2017. A simplified Hummer's method was successfully used in synthesising graphene oxide nanoplatelets. These nanoplatelets were synthesised at room temperature at various processing times (24 h, 72 h, and 120 h). Ultraviolet visible spectroscopy (UVvis) showed that all synthesised graphene oxide nanoplatelets suspensions have similar broad shoulder absorbance at a wavelength of 300 nm. Furthermore, similar functional groups were detected by Fourier transform infrared spectroscopy (FTIR) across all types of graphene oxide nanoplatelets structures. The effect of processing time on the thickness of the sheet size was interpreted through topology using atomic force microscopy (AFM). The structural properties of graphene oxide nanoplatelets were evaluated using X-ray diffraction (XRD). The results showed a slight increase in the interlayer spacing with no sharp distinction in the crystallinity for graphene oxide nanoplatelets at longer processing times. The ratio of carbon to oxygen composition on the surface of each synthesised graphene oxide nanoplatelet was computed using the X-ray photoelectron spectroscopy (XPS). Field emission scanning electron microscopy (FESEM) was used to determine the morphology of the nanoplatelets. Three steps of degradation occurred during the thermogravimetric analysis (TGA). Degradation peaks were identified using differential scanning calorimetry (DSC). Electrical properties were characterised using the four-probe conductivity method. It can be concluded that properties such as sheet size, thickness, morphology and electrical conductivity of the graphene oxide nanoplatelets can be tuned by varying the processing time while maintaining its chemical characteristics.